PENGEMBANGAN KOMIK PEMBELAJARAN MATERI INTERAKSI MAKHLUK HIDUP DENGAN LINGKUNGAN UNTUK KELAS VII SMP - Lanis Nopita Maini; Rivo Yulse Viza; Arista Ratih (BIOCOLONY, 2021)
This research is motivated by the unavailability of interesting learning media. So far, teachers only use textbooks and worksheets, so researchers want to develop comics as a support for integrated science teaching and learning activities at SMP Negeri 42 Merangin. This study aims to describe the process of developing comics on the material of the interaction of living things with the environment and to find out which comics on the material of interactions of living things with the environment are valid and practical. This type of research is a development research that uses a 4-D model which includes the define, design, develop, and disseminate stages. The subject of this research is the Integrated Science teacher at SMP Negeri 42 Merangin. Based on the results of the research, a product in the form of learning comics was produced. The resulting learning comics were declared very valid by the validator from the aspect of the feasibility of content, language, presentation, and graphics with a validity value of 91.5%. The resulting learning comics were also stated to be very practical by the teacher both in terms of ease of use, learning time, and attractiveness with a score of 3.7. So it can be concluded that the learning comics on the interaction of living things with the environment for class VII SMP/MTs have been declared valid and practical.